The possible mechanism of hydroxytyrosol on reducing uric acid levels. (March 2018) - Wan, Yin; Liang, Yu-Xi; Zou, Bin; Fu, Gui-Ming; Xie, Ming-Yong
Highlights: XOD activity could be restrained by hydroxytyrosol in vivo and in vitro . The mechanism of molecular interaction between XOD and hydroxytyrosol was discussed. Hydroxytyrosol could reduce uric acid level in hyperuricaemia rat serum. Hydroxytyrosol could adjust the genes mRNA of renal uric acid transporter. Abstract: In this study, the inhibitory effect of hydroxytyrosol against xanthine oxidase (XOD) by in vivo animal model and in vitro inhibition assay was analysed. The results showed that hydroxytyrosol could reduce uric acid in rat serum, inhibit XOD activity in rat liver, and adjust the mRNA transcription of the renal uric acid transporters URAT1, GLUT9, OAT1, UAT and ABCG2 towards normal in the transcription level. Hydroxytyrosol was observed as an inhibitor of XOD activity, which's IC50 value of restraining XOD activity was 8.75 mM. Circular dichroism (CD) spectroscopy indicated that the secondary structures of XOD were changed after incubation with hydroxytyrosol. The docking simulation showed that hydroxytyrosol could enter into the active site of XOD and form hydrogen bonds with amino acid residues (such as ARG880, GLU1261 and THR1010). The results suggested that hydroxytyrosol could be a potential XOD inhibitor for hyperuricaemia treatment.